Psychosocial impact of climatotherapy in young patients with psoriasis: a 3-month cohort study - Max Nordgren; Max Nordgren; Albert Duvetorp; Albert Duvetorp; Albert Duvetorp (Frontiers in Medicine)
Ultraviolet rays are known to have positive effect on psoriasis, but the cold climate and latitude in Northern Europe reduce access to the sun. Climatotherapy is a treatment modality where the patient is relocated to a warmer region with a high ultraviolet (UV) index. Young patients with psoriasis can be particularly burdened by the disease, and studies have shown an association between psoriasis and mood disorders. Patients who have undergone climatotherapy often report beneficial psychological effects after treatment, but this has not yet been studied. To explore the psychosocial impact of climatotherapy, an observational study was designed. Thirty-four participants (median age of 24 years) underwent 3 weeks of treatment in Gran Canaria (Spain) and responded to questionnaires assessing the psychosocial aspects of the disease. Climatotherapy was associated with significantly reduced scores of HADS, PSS-10, PSQ, EQ-VAS, DLQI, and itch intensity at the end of and at 3 months after the end of treatment compared to before treatment onset. The results suggest that climatotherapy not only exerts effects on psoriasis skin disease but also improves symptoms of anxiety, depression, perceived stigmatization, stress, quality of life, self-assessed overall health perception, and itch intensity. The results can be of use in the decision-making process when choosing a suitable treatment for young patients with psoriasis.